PENGARUH JUMLAH PENDUDUK, UPAH MINIMUM, DAN PDRB TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI SUMATERA UTARA - Syafira, Syarifah; Selvia, Dina (LPPM UNIMAL, 2023)
The study is aimed at recognizing the impact of population size, minimum wage and GRDP on the participation rate of the labor force in the Northern Sumatra Province. The data used in this study is a combination of the time series and cross section at 2017-2021. The data obtained in this study is from the statistical center (BPS) of 30 Districts/Northern Sumatera Province. The best model chosen in this study is the Random Effect Model (REM). Partially population and Gross Regional Domestic Product (GRDP) positive and significant effect on the level of labor force participation rate, minimum wage has positive and no significant impact on the labor force participation rate. Population, minimum wage and GRDP simultaneously have a positive and significant effect on the labor force participation rate.